Dairy information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Interested in getting hands-on information for dairy projects? Despite the recent growth in dairy development programmes in many countries at local and national levels, and their associated networks, most of the reliable information sources are...